Screening first-degree relatives of patients with Chronic Kidney Disease (CKD) in Pakistan - Ilyas, Amna; Ali, Bakhtawar (Journal of the Pakistan Medical Association, 2024)
Dear Sir / Madam Chronic Kidney Disease (CKD) poses a worldwide health concern, affecting more than eight hundred million people globally, with underdeveloped nations sharing the greatest disease burden.1 It’s hypothesised that by 2030, countries with less than 15% of the economy will account for over 70% of the patients with ESRD. 2 Therefore, early detection through targeted screening is crucial in developing countries like Pakistan. However, owing to racial and ethical differences in results, the Kidney Disease Prevention Network unanimously agreed that each country, based on the prevalence of risk factors at a local level, must delineate their own high-risk groups to be screened.2 Recent studies in Pakistan3,4, like those in India5, Nigeria6, and China7, have shown evidence of clustering of CKD in first-degree relatives, making them an important target population for screening. Nonetheless, due to the lack of proper screening in Pakistan, there are delays in management as well as referrals to nephrologists, even among individuals with a strong family history of CKD. In Pakistan, where access to dialysis therapy is already limited due to the continuously increasing per-person cost of dialysis and lack of availability, we must shift the focus towards screening high-risk populations to prevent strain on the economically vulnerable. The targeted screening of first-degree relatives will not only save millions spent on dialysis and renal transplants but will also reduce the recruitment costs of screening as the family members are in constant contact with the healthcare system. Moreover, since they’re also firsthand witnesses to the financial and physical impact of delayed diagnosis, family members of CKD feel more motivated to actively participate in screening programmes. Considering the above, it is imperative to conduct more extensive clinical trials and assess the efficacy of screening, including opportunistic screening in dialysis units as well as outdoor settings, of first-degree relatives in Pakistan.